The Influence of Social Media Marketing, Online Customer Review and Brand Image on Purchase Decision in the Tiktok Application for Muslim Fashion Products - Millenia, Mita; Widarta (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to find out whether there is an influence of Social Media Marketing, Online Customer Reviews and Brand Image on Purchase Decisions on the TikTok Application for Muslim Fashion Products. The subjects of this research were users from Management students at the Faculty of Economics, Mercu Buana University, Yogyakarta. The sample in this study amounted to 105 respondents. The research analysis method was carried out using multiple linear regression and analysis techniques using IBM SPSS 22 software. Based on the research results, it was found that social media marketing and brand image had a positive and significant effect on purchase decision, online customer reviews did not have a positive and significant effect on purchase decisions.